Trends of dental stem cells research—A bibliometric analysis and visualization - Namrata Dagli, Santosh Kumar, Rohan Bhatt, Govindool Sharaschandra Reddy, Rahnuma Ahmad, Mainul Haque, (Journal of Applied Pharmaceutical Science, 2024)
This study aims to provide a comprehensive overview of the research landscape surrounding dental stem cells (DSCs), elucidating the key contributors, institutions, and countries, their collaborations, thematic evolution, and research trends. An online electronic search was performed on 24 July 2023 in the PubMed database to identify the research done on DSCs. The search strategy used was -(Stem cells) AND (Dental pulp OR periodontal ligament OR deciduous teeth OR apical papilla OR dental follicle stem cells). Article types included were review articles, clinical trials, meta-analyses, and book chapters. No filter was applied for species, language, gender, journal, age, or publication date. Network analysis and visualization were done with the help of the VOSviewer software (version 1.6.18) and Biblioshiny. 6,685 results appeared from an online search in the PubMed database. Of these 34 clinical trials, 867 reviews and systematic reviews, 14 meta-analyses, 6 books and documents. A gradual increase in the number of research papers during the last two decades, ranging from 6 papers in 2000 to 872 articles in 2022, was observed. The analysis identified China as the most productive country, the Journal of Endodontics as the most relevant source, and Sichuan University as a top contributor with 1,666 publications on DSC research. According to the analysis, cell differentiation is the keyword specific to the field with the highest co-occurrence. Wang Y, Zhang Y, and Liu Y were identified as the most relevant authors, with 175, 171, and 166 papers. Collaboration frequency between China, Japan, and the United States of America is comparatively higher than in other countries. A gradual increase in publishing trends can be noticed during the last two decades. Most of the papers on DSCs are single-country publications. This analysis highlights the transition in research from sialoproteins to more application-based, such as tissue engineering and periodontal ligament.
Keywords: Bibliometric, network analysis, dental stem cells, network visualization